Errors of Pronoun Usage among Nigerian Secondary School Students - Olusegun O. Jegede; Akintunji M. Akinola (Britain International for Academic Research (BIAR-Publisher), 2021)
This study examined the errors of pronoun usage among Nigerian Secondary School Students. The study looked specifically at pronoun types, and identified and examined the errors that secondary school students make in their use. The research subjects were students of public secondary schools in Oyo West Local Government Area. There are fifteen (15) public secondary schools in the Local Government Area. However, out of the fifteen (15) public secondary schools, five (5) were chosen. The researcher made use of stratified sampling technique in order to classify the respondents’ view into different characteristics for clear and better results. A total of one hundred (100) students were selected for the study, with twenty (20) students selected from each school. Test questions with options were designed specifically for the students in the selected schools. The test questions focused on all the aspects of pronoun usage, especially the areas where students make errors such as subjective case pronouns, objective case pronouns, possessive case pronouns and tactic pronouns. The test was adequately supervised to see that the respondents did not consult their mates for any assistance before they could respond to the test. It was administered in the classroom for their convenience and proper supervision. There were twenty (20) questions in the test, four questions each were on the subjective case, objective case, possessive case, problematic pronouns usages and unique pronouns types (indefinite pronoun and reciprocal pronouns). At the end, the test scripts were collected and marked. The errors made were identified and categorised and examined. The study clearly showed that secondary school students in Nigeria use pronouns that are inaccurate or incorrect in their expressions. In this vein, the study showed that these errors occur because the students have not fully learned the correct use of the pronouns. The study also found that the teaching method applied in the teaching of English grammar in secondary schools is not very effective and English language teachers need to set up a workable teaching and evaluation method that will show how well a learner has learned. The study concluded that the students need constant exposure to the English language to fully develop communicative competence in it.